MANFAAT PEMBELAJARAN PENDIDIKAN PANCASILA TERHADAP RASA NASIONALISME MAHASISWA FPBS UPI - Adib Amrullah; Muhammad Alfath Firasy Purnama, Nanda Lestari, Renren Nurfauziah, Supriyono (JURNAL PENDIDIKAN DAN KEGURUAN, 2023)
This research aims to determine the benefits of Pancasila education on the sense of nationalism in students at the Faculty of Language and Literature Education at the University of Indonesia. This research discusses the Pancasila Education course and the sense of nationalism of students who choose the language and literature study program. The many challenges to maintaining a sense of nationalism caused by foreign cultures studied in the language and literature study program make students more familiar with foreign cultures than local cultures. Pancasila education has the benefit of maintaining students' sense of nationalism, through learning Pancasila Education which contains the introduction and efforts to maintain a sense of nationalism in students. Nationalism can be triggered by several factors, it can be based on national spirit, national character, national level, national language, national equipment, and religion. Pancasila education can be one of the supporting factors for the growth of students' sense of nationalism. Based on the results of research conducted using questionnaires distributed to students at the Faculty of Language and Literature Education, Indonesian Education University, learning Pancasila Education has an influence on students' sense of nationalism. Students agree that the existence of Pancasila education has benefits for the level of nationalism of language and literature education students at the Indonesian University of Education.